Comparison of virulence-related determinants between the ST59-t437 and ST239-t030 genotypes of methicillin-resistant Staphylococcus aureus - Feng Liao; Wenpeng Gu; Xiaoqing Fu; Bin Yuan; Yunhui Zhang (BMC Microbiology, 2021)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is an important pathogen for human infection. Hospital-acquired (HA) and community-acquired (CA) MRSA infections are serious clinical problems worldwide. In this study, we selected typical HA-MRSA strain and CA-MRSA isolates from our previous research and compared their phenotypic and pathogenic abilities both in vitro and in vivo. Results ST59-t437-SCCmecIVa (YNSA7) and ST59-t437-SCCmecVb (YNSA53) belonged to two prevalent subclones of CA-MRSA, while ST239-t030-SCCmecIII (YNSA163) was an HA-MRSA epidemic clone in Southwest China. ST59-t437 strains demonstrated faster growth ability, higher survival rate resistance to human blood, and more toxin secretion levels and cytotoxicity than ST239-t030. The virulence and regulatory genes of hld, psm-α, RNAIII, agrA, and crtN were highly expressed on CA-MRSA isolates, especially the ST59-t437-SCCmecIVa subclone. However, the ST239-t030 strain had the strongest adhesion and biofilm ability among these MRSA bacteria. Animal experiments revealed the most serious lethal effect on BALB/c mice caused by the YNSA7 strain infection. The survival rates of BALB/c mice infected with the three MRSA strains were 16.7, 50.0 and 100.0% for YNSA7, YNSA53 and YNSA163, respectively. Histopathological analyses of infected animals indicated that the lungs were the most seriously damaged organs, especially for ST59-t437 MRSA. Severe inflammatory reactions, tissue destruction, and massive exudation of inflammatory mediators and cells could be identified in ST59-t437 strain-infected animals. Conclusions In general, ST59-t437 strains showed higher pathogenic ability than the ST239-t030 isolate, while ST239-t030 MRSA revealed the features prevalent in hospital settings, specifically for adhesion and biofilm ability.